The impact of quantitative easing on commercial banks: evidence from the Euro Area - Montez, Filipa Alves (2018)
Most of the studies tend to analyze the impact of quantitative easing (QE) on financial markets and at a macroeconomic level, not giving enough attention to the impact of this unconventional monetary policy on commercial banks. The impact of QE on 24 commercial banks based on the Euro Area will be investigated in this study, using publicly available panel data. This work project suggests that the European Central Bank’s (ECB) QE purchases, since the start of the program in January 2015, had a statistically significant increase but small effect in the growth of bank’s loans. Moreover, through a robustness check, it is observed that QE’s impact is bigger in small banks.